Pengembangan E-Book Pahlawan Nasional Indonesia Dalam Sorotan Sejarah Menggunakan Android Studio: e-book, Pahlawan Nasional, sejarah, Android Studio, media pembelajaran - Hidayat, Kemas Muhammad Wahyu (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2025)
This study aims to develop an e-book on the theme of Indonesian National Heroes in the spotlight of history, utilizing the Android Studio platform as a technology-based learning medium. This e-book is designed to provide an interactive, informative, and easily accessible learning experience for students and the general public. The research method used is Research and Development (R&D), which adapts the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. In the analysis stage, user needs related to historical materials and supporting technology were identified. The design stage involved creating a storyboard and e-book layout to ensure the content presented was in line with the curriculum and visually appealing. Development was carried out by utilizing Android Studio features, such as multimedia integration (text, images, videos) to enhance user understanding. A limited trial was conducted on high school students, followed by an evaluation to measure the application's effectiveness and appeal. The results showed that this e-book successfully met the needs of digital-based learning and received a positive response from users. This e-book was considered easy to use, informative, and capable of increasing interest in learning history, particularly about the important role of national heroes in the Indonesian struggle. These findings provide a significant contribution to the development of modern learning media relevant to the needs of today's digital generatio